119k views
0 votes
Solve each system of equation using Subtitution
Y=x
Y=-x+2

1 Answer

3 votes

Answer:

(1, 1 )

Explanation:

Given the 2 equations

y = x → (1)

y = - x + 2 → (2)

Substitute y = x into (2)

x = - x + 2 ( add x to both sides )

2x = 2 ( divide both sides by 2 )

x = 1

Substitute x = 1 into either of the 2 equations for y

Substituting x = 1 in (1)

y = 1

Solution is (1, 1 )

User Expurple
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.